Development of a hydrate formation prediction model for sub-sea pipeline - Abbasi, A. (Taylor and Francis Inc., 2017)
In this research work, a novel model is developed to the hydrate formation pressure and hydrate formation temperature for a single component of methane (CH4) gas. This research model holds at a temperature and pressure of real-time data for pure water, methane, and other mixtures of gases, respectively. Furthermore, the modelling and statistical analysis conducted in this research were divided into three major segments; the assessment of the computability of the mathematical models, the performance of the proposed optimization techniques, and the comparison of the proposed techniques with real-time data of gas pipeline. Results showed that the improved optimization algorithms are in admirable compliance with the real-time data. These correlations are providing the capability to predict gas-hydrate-forming conditions for a wide range of hydrate formation data. © 2017 Taylor & Francis Group, LLC.